STUDI EKSPERIMEN PENGARUH POROSITY RATIO PADA PERFORATED TWISTED TAPE INSERT TERHADAP KARAKTERISTIK HEAT TRANSFER DAN FRICTION FACTOR PADA PENUKAR KALOR PIPA GANDA - Puspitasari, Susi; Safitra, Arrad Ghani (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
Heat exchanger is used device to transfer thermal energy (enthalpy) between two or more fluids at different temperatures. One type of heat exchanger is double pipe heat exchanger. Double pipe heat exchanger consists of one pipe placed concentrically in another pipe with a larger diameter. One fluid passes through the inner pipe and the other fluid passes through the outer pipe (annulus). Performance of double pipe heat exchangers can be determined based on the characteristics of heat transfer and friction factor. One effort to improve the performance of double pipe heat exchanger can by passive method which is adding perforated twisted tape in the inner pipe. Perforated twisted tape had three different porosity ratios, that is 1.88, 3.77, and 5.65% that comparison with plain twisted tape (porosity ratio 0). Fluid flowed in double pipe heat exchanger is water in liquid phase in laminar-transition flow regime. Reynolds number in annulus is made constant at 2000, while in inner pipe is 1000-5000. Temperature of water entering annulus and inner pipe is kept constant at 20ÂºC and 50ÂºC, respectively. From the experimental results it found that perforated twisted tape increased Nusselt number and friction factor values respectively 0.1-0.8% and 203-1536% higher than double pipe heat exchanger without twisted tape (plain tube). Perforated twisted tape with porosity ratio 3.77% has the best performance, that is increasing Nusselt number average of 0.31% from 28.8913 in plain tube to 28.9810 and increasing friction factor average of 366.34% from 0.6521 in plain tube to 3.0410.